EFEKTIVITAS PENYELENGGARAAN PROGRAM BIDIKMISI DI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS UDAYANA - kadek wiwin wismayanthi; Putu Eka Purnamaningsih (Universitas Mahendradatta Denpasar, 2021)
The implementation of the bidikmisi education fee assistance program is a step taken by the government to provide access to higher education to all people. This program is implemented by prioritizing the 3T principle, namely right on target, on time and in efficiency. This program is inseparable from various obstacles and obstacles to achieving the vision and mission and objectives of its implementation. These problems and obstacles also occur at Udayana University as one of the state universities that organizes the Bidikmisi education fee assistance program. Problems that occur include inaccurate provision of funding assistance, delays in disbursement of funds and unattainable objectives of program implementation. This research was conducted to determine the effectiveness of the implementation of the bidikmisi education fee assistance program at the Faculty of Social and Political Sciences, Udayana University using a case study with a qualitative descriptive research type. The unit of analysis in this study is all parts involved in the implementation of the bidikmisi education fee assistance program. The data collection technique was carried out by means of field studies, namely data collection, observation, interviews and documentary studies. The results of the analysis show that in the implementation of the bidikmisi education fee assistance program at the Faculty of Social and Political Sciences, Udayana University, there are obstacles and obstacles, namely the distribution of aid that has not been on target, the distribution of education costs is not yet on time, the lack of coordination between the program organizers. Therefore, it is still necessary to make improvements in several aspects such as improving the quality of selection of prospective recipients of bidikmisi tuition assistance, increasing coordination between the central government, state tertiary institutions and banks in the process of distributing assistance and increasing internal university coordination to achieve the vision and mission and objectives. the implementation of the bidikmisi education fee assistance program.